Analisis Rasio Likuiditas Dan Rasio Solvabilitas Terhadap Profitabilitas Pada Perusahaan Sub Sektor Food & Staples Retailing - Dina Nurseva Putri; Yeni Rafika Nengsih; Anne Putri (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of liquidity ratios and solvency ratios on profitability in companies within the Food and Staples Retailing sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. The independent variables in this study are Current Ratio (CR) and Debt to Equity Ratio (DER), while the dependent variable is Return on Assets (ROA). The study uses secondary data in the form of annual company financial reports, employing multiple linear regression analysis and purposive sampling techniques for sample determination. The results indicate that partially, CR has a positive and significant effect on ROA, while DER has a negative and insignificant effect on ROA. Simultaneously, CR and DER influence ROA. The coefficient of determination value shows that the independent variables can explain part of the profitability variation, while the rest is influenced by other variables outside the research model. This study concludes that good capital structure management plays a role in maintaining the company's profitability level.